Charge Capacitance and Hydrogen Storage Capacity of Drop Cast and Electrodeposited Reduced Graphene Oxide Coatings. Issue 9 (2nd September 2021) - Avraham, Hanan; Kadosh, Yanir; Korin, Eli; Bettelheim, Armand
Abstract : Drop cast (DC) and electrodeposited (ED) graphene-based coatings on glassy carbon (GC) electrodes were subjected to various electro-reduction degrees. The ED coatings were characterized by more accumulated graphene sheets imperfections as observed by cross section TEM analysis. These coatings, when reduced at −1.6 V vs Hg/HgO showed more efficient removal of phenolic groups than DC ones treated at the same potential (remaining contents of 2.1 and 18.1%, respectively). They also showed lower charge transfer resistance (5.2 and 28 Ω cm 2, respectively), higher capacitance (73.2 and 42.6 F g −1, respectively), and higher hydrogen storage capacity (119 and 57 mAh g −1, respectively). Moreover, they showed higher stability towards H2 charge/discharge cycles (retained hydrogen capacities of 95 and 40% after 15 and 6 cycles for ED and DC coatings reduced at −1.5 V, respectively). The superior performance properties of coatings obtained by ED and subsequently electro-reduced make them promising electrode materials for energy storage.